2022
DOI: 10.3389/fgene.2022.916867
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of the Class III Peroxidase Gene Family in Tobacco (Nicotiana tabacum)

Abstract: Class III peroxidases (PODs) are plant-specific enzymes that play significant roles in plant physiological processes and stress responses. However, a comprehensive analysis of the POD gene family in tobacco has not yet been conducted. In this study, 210 non-redundant POD gene members (NtPODs) were identified in tobacco (Nicotiana tabacum) and distributed unevenly throughout 24 tobacco chromosomes. Phylogenetic analysis clustered these genes into six subgroups (I-VI). Gene structure and motif analyses showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 82 publications
3
13
0
Order By: Relevance
“…However, tandem and segmental duplications are the primary reasons for expanding the class III PRX gene family in maize ( Wang et al., 2015 ) and pineapple ( Hou et al., 2022 ). Segmental duplication is the main reason for the expansion of the class III PRX gene family in tobacco ( Cheng et al., 2022 ), soybean ( Aleem et al., 2022 ), and potato ( Yang et al., 2020 ). These results indicated that tandem and segmental duplications were pivotal in expanding plants’ class III PRX gene family.…”
Section: Discussionmentioning
confidence: 99%
“…However, tandem and segmental duplications are the primary reasons for expanding the class III PRX gene family in maize ( Wang et al., 2015 ) and pineapple ( Hou et al., 2022 ). Segmental duplication is the main reason for the expansion of the class III PRX gene family in tobacco ( Cheng et al., 2022 ), soybean ( Aleem et al., 2022 ), and potato ( Yang et al., 2020 ). These results indicated that tandem and segmental duplications were pivotal in expanding plants’ class III PRX gene family.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the seedlings were grown in plastic pots with a 16-h light cycle at 28°C during the day and 23°C at night. Similar with our previous study [ 65 ], root, stem, leaf, bud tissues at seedling stage (SS), vigorous growth stage (VG), and flowering stage (FS), as well as petal, receptacle, stamen, and pistil samples of reproductive organs (RO), were collected from tobacco. The drought and cold stress were conducted during the vigorous growth stage of tobacco.…”
Section: Methodsmentioning
confidence: 93%
“…Purifying selection has been a common feature in the evolution of plant PRX genes. Duplicated PRX genes in maize (Wang et al 2015), pear (Cao et al 2016), wheat (Yan et al 2019), Brachypodium distachyon (Zhu et al 2019), grapevine (Xiao et al 2020), carrot (Meng et al 2021), birch (Cai et al 2021), tobacco (Cheng et al 2022), and cotton (Chen et al 2022) were all predominantly subjected to purifying selection, indicating that the gene family has undergone relatively conservative evolution with stable structure and function. The PpPRX family was not an exception and all duplicated pairs but one were subject to negative selection.…”
Section: Discussionmentioning
confidence: 99%
“…A few examples of PRXs whose functions were studied by reverse genetics are: Arabidopsis PRX2, PRX25 and PRX71 in lignification (Shigeto et al 2015), a pepper PRX (CaPO2) in ROS generation and disease resistance (Choi et al 2007), and Arabidopsis PRX16 in seed germination (Linkies et al 2010). Due to their diverse roles in plant growth and development as well as in defense responses, PRX families have been identified and characterized in model plants or major crops, including Arabidopsis (Tognolli et al 2002; Welinder et al 2002), rice (Passardi et al 2004), poplar (Ren et al 2014), maize (Wang et al 2015), pear (Cao et al 2016), switchgrass (Moural et al 2017), wheat (Yan et al 2019), cotton (Chen et al 2022), grapevine (Xiao et al 2020), potato (Yang et al 2020), soybean (Aleem et al 2022), and tobacco (Cheng et al 2022).…”
Section: Introductionmentioning
confidence: 99%